Algorithm Development and Design of Lattice Conical Shell Under Mechanical and Thermal Loads - Behrooz Shahriari; Mahdi Sharifi; Hassan Izanlo (International Journal of Advanced Design and Manufacturing Technology)
In this study, the development of a generative algorithm related to the lattice conical shell (Isogrid pattern) and the modeling of the stiffened shell under mechanical and thermal loads are discussed. An algorithm has been developed for the lattice conical shell (MATLAB software), which generates the pattern of stiffeners on the conical shell. Modeling of the lattice conical shell is done in SolidWorks software. The structure of stiffened shell is analyzed under loading using the Finite Element Method (FEM) in the ANSYS Workbench. The modeling of the lattice conical shell is investigated under mechanical (axial and bending load and internal pressure) and thermal loads. It is concluded that the stiffeners can resist buckling and mechanical failure under mechanical and thermal loading conditions, while the mass is significantly reduced. This shell can be used in various industries due to its lightweight and high resistance. Whereas the safety factor of the final model is about 2 and the model is acceptable for desirable internal pressure (0.6 MPa), the total system mass is about 41 kg.